Bytový dům - Šlézarová, Aneta (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Předmětem bakalářské práce je novostavba bytového domu a vypracování dokumentace pro provádění stavby. Bytový dům je umístěn na okraji města Rožnov pod Radhoštěm. Zástavbu tvoří bytové domy. Objekt je samostatně stojící podsklepený a se čtyřmi nadzemními podlažími. Bytové jednotky mají převážně dispozici 2+kk, ve 4NP se nacházejí dva byty s terasami. Objekt je bezbariérově přístupný pomocí svislé plošiny. Svislé nosné konstrukce v nadzemních podlažích tvoří keramické tvárnice Porotherm, v suterénu jsou vyzděny ze ztraceného bednění. Vodorovné konstrukce jsou z monolitických železobetonových desek. Objekt je zastřešen plochou střechou a založen na základových pasech.

The subject of this thesis is a new build of a block of flats and drawing up documentation necessary to carry out the construction. The block of flats is located on the edge of the town of Rožnov pod Radhoštěm. The housing development consists of blocks of flats. The building is a stand alone building with a cellar and has 4 above-ground floors. The flats predominantly comprise of 2 rooms and a kitchenette and on the 4th floor there are 2 flats with a terrace. The building is wheelchair accessible using a vertical ramp. The vertical structure frame on the above-ground floors is made of Porotherm ceramic blocks and in the basement they are bricked up with formwork. The horizontal construction is made of monolithic reinforced concrete slabs. The building has a flat roof and is supported by footings.
Apartment building
Keywords: Bytový dům; Porotherm; základové pasy; železobetonové stropy; bezbariérový přístup; block of flats; Porotherm; footings; reinforced concrete ceiling; wheelchair accessible